A spontaneous retroperitoneal haemorrhage resulting in abdominal compartment syndrome requiring laparotomy: A case report and proposed management algorithm. (July 2021) - Tully, Patrick; Moshinsky, James; Spanger, Manfred; Koshy, Anoop N.; Yii, Michael; Weinberg, Laurence
Abstract: Introduction and importance: Spontaneous Retroperitoneal Haemorrhage (SRH) is a rare condition, which in its extreme state can result in Abdominal Compartment Syndrome (ACS). The aim of this case report is to provide an overview of the diagnosis and management of SRH and to present an algorithm to inform and guide clinical decision-making in the context of ACS. Case presentation: A 74-year-old woman with multiple risk factors for SRH developed a tense abdomen in ICU post-cardiac graft study. Radiological imaging confirmed multiple bleeding points to the contralateral side of the graft access site. She underwent endovascular treatment for her condition, however, developed ACS necessitating surgical evacuation of the haematoma. Clinical discussion: SRH is a rare condition that may be difficult to diagnose on physical exam. Medical, endovascular and surgical approaches are recognised treatments. ACS is an extreme variant of SRH and although endovascular management can specifically address the acute bleed, surgical evacuation of the haematoma is the only treatment that can effectively reduce abdominal compartment pressures. Conclusion: SRH can cause abdominal compartment syndrome with subsequent multiorgan failure. Ultimately, as outlined in this case, surgical evacuation of the haematoma was the only treatment able to reduce abdominal compartment pressures. Highlights: Retroperitoneal haemorrhage can cause ACS and multiorgan failure. Medical, endovascular and surgical approaches are recognised treatments. Endovascular management should be considered in patients with ongoing bleeding. Endovascular approaches may cease bleeding but not alleviate any mass effects. Surgical management is indicated if conservative or endovascular measures fail.